2005
DOI: 10.1529/biophysj.104.052100
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hydrophobicity to Thermodynamics of Ligand-DNA Binding and DNA Collapse

Abstract: The importance of understanding the dynamics of DNA condensation is inherent in the biological significance of DNA packaging in cell nuclei, as well as for gene therapy applications. Specifically, the role of ligand hydrophobicity in DNA condensation has received little attention. Considering that only multivalent cations can induce true DNA condensation, previous studies exploring monovalent lipids have been unable to address this question. In this study we have elucidated the contribution of the hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 62 publications
6
68
0
Order By: Relevance
“…In all clear and transparent preparations, intensity values resulting from Fatty acid-spermine conjugates as DNA carriers JR Viola et al light scattered by particles with diameters larger than 1 mm were neglected, as this light scatter most probably results from dust particles. 18,23 Most of the formulations presented a relatively broad population distribution, except for decanoylspermine/DNA 1:1 ( Figure 5). An increase in the concentration of butanoylspermine in the formulation of DNA complexes resulted in the formation of more stable colloidal solutions, as evidenced by a decrease in the average particle diameter, together with an increase in light intensity ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In all clear and transparent preparations, intensity values resulting from Fatty acid-spermine conjugates as DNA carriers JR Viola et al light scattered by particles with diameters larger than 1 mm were neglected, as this light scatter most probably results from dust particles. 18,23 Most of the formulations presented a relatively broad population distribution, except for decanoylspermine/DNA 1:1 ( Figure 5). An increase in the concentration of butanoylspermine in the formulation of DNA complexes resulted in the formation of more stable colloidal solutions, as evidenced by a decrease in the average particle diameter, together with an increase in light intensity ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Polyamines have been extensively used for the development of nonviral vectors and this includes studies in which lipospermines typically either contain double or have longer hydrocarbon chains. 18,21,[28][29][30][31] It has previously been suggested that DNA-binding affinity is a function of both charge and hydrophobicity. 19,32 However, to what degree this affinity is beneficial for gene delivery is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the observed binding enthalpy can be parsed into two contributions: (3) whereΔH pe is assumed to be essentially zero [53], and ΔH t equal to ΔH obs . For poly(dA)·poly (dT) binding with DB75, ΔH t was obtained as 3.1 kcal mol −1 , while for poly(dA-dT)·poly(dAdT) binding with DB75, ΔH t was obtained as −4.5 kcal mol −1 .…”
Section: Discussionmentioning
confidence: 99%